Triceratops : the last dinosaur - Sandell, Elizabeth J.; Oelerich, Marjorie L.; Schroeder, Howard; Vista III Design (Mankato, MN, U.S.A. : Bancroft-Sage Pub., 1988)
Presents presently-known information on the plant-eating dinosaur that looked like a rhinoceros.
13 36
Keywords: Triceratops -- Juvenile literature; Triceratops; Dinosaurs